Mangoldia, a new lichen genus in the family Graphidaceae (Ascomycota: Ostropales) - Lücking, Robert; H., Sittiporn Parnmen; Lumbsch, Thorsten (Phytotaxa, 2012)
The new genus Mangoldia Lücking, Parnmen & Lumbsch is described based on the new species M. australiana and also including M. atronitens. Mangoldia combines thallus and ascoma features of Phaeographis s.str. (e.g., P. dendritica and P. lecanographa), i.e. a white, ecorticate thallus and ascoma with exposed, brown disc and thin, partially split, thalline margins, with hymenial and ascospore characters of Graphis, i.e. distoseptate, hyaline ascospores which react I+ violet-blue. DNA sequence data of the nuclear large subunit ribosomal DNA (nuLSU) of M. australiana place the taxon as separate lineage within subfamily Graphidoideae tribe Graphideae, but without a resolved and supported sister-group relationship with any of the accepted genera in this tribe.